Hacia una sociedad feliz: la utopía de un ideal - Casasola Rivera, Wílmer (2014)
This paper describes the foundations of a happy society, according to the work Utopia by Thomas More (1478-1535). The purpose is to focus on three key issues, specifically, the governor tasks in the fair fulfillment of his duties at the service of society, the crucial role of education as a tool to raise awareness of social reality, and the common good, a fundamental principle for a happy society.